Innovation of Fisheries Technology for the Development of Tarikolot Tourism Village - Usep Suhendar; Linda Jati Kusumawardhani; Pandri Ferdias (FOUNDAE (Foundation of Advanced Education), 2021)
Tarikolot Tourism Village is one form of community empowerment that is quite good in the city of Bogor. The use of sleeping land in these locations by community residents, especially the Tarikolot United Youth Association and Ciluar Tourism Conscious Group (Pokdarwis), into productive activities such as fisheries and livestock, can be a pilot for other regions. However, the results obtained are still less than optimal because no touch of technological innovation can optimize the potential. The purpose of this activity is to provide technical innovations in the field of fisheries and livestock for the development of Tarikolot tourism village, including tilapia and catfish cultivation systems in bioflocs and aquaponics, automatic feeder machines, water pumps, versatile enumeration machines, solar power plants, solar public street lighting (PJU-TS), and planting Family Medicine Plants (TOGA) and fruits on site. The technological innovations were designed jointly between the proposing team from Pakuan University with both partners to be installed at the location. The method used is a Forum Group Discussion and workshop with a Community Development approach. The impacts resulting from this activity are (1) Partners can increase food availability in urban land. (2) The provision of capital assistance for the buyer of fish seedlings is expected by partners also to be able to supply food for the area and increase partners' income. and (3) With training, partners are expected to increase knowledge about fish and vegetable cultivation systems through aquaponics technology and bioflocs ponds, running the technology system well without any constraints in the field